Oscar Milosz: Poetic Topicality of Adventure - Skurdenienė, Irena (Respectus Philologicus, 2003)
The paper is based on Oscar Milosz’s words that "poetry is the ruler of archetypes". This quotation gives a possibility to analyze poetry taking into consideration the conventions of adventure that are closely related to the archetypical structures. O. Milosz is said to have inherited "the gene of adventure" from his ancestors. On the figurative text level he often introduces himself as a traveling knight or as a troubadour. Nevertheless, this is only a metaphysical travel in the past. Using G. Deleuze’s terminology we can talk about a specific O. Milosz’s spiritual kinship with Robinson Crusoe and present him as a person creating a mysterious metaphysical space where he tries to avoid abstractions and to reveal his philosophical thought with the help of concrete physical reality.